Skills, Majors, and Jobs: Does Higher Education Respond? - Johnathan G. Conzelmann; Steven W. Hemelt; Brad J. Hershbein; Shawn Martin; Andrew Simon; Kevin Stange (Institute of Labor Economics (IZA), 2023)
How do college students and postsecondary institutions react to changes in skill demand in the U.S. labor market? We quantify the magnitude and nature of response in the 4-year sector using a new measure of labor demand at the institution-major level that combines online job ads with geographic locations of alumni from a professional networking platform. Within a shift-share setup, we find that the 4-year sector responds. We estimate elasticities for undergraduate degrees and credits centered around 1.3, generally increasing with time horizon. Changes in non-tenure-track faculty allocations and the credits they teach partially mediate this overall response. We provide further evidence that the magnitude of the overall response depends on both student demand and institutional supply-side constraints. Our findings illuminate the nature of educational production in higher education and suggest that policy efforts that aim to align human capital investment with labor demand may struggle to achieve such goals if they target only one side of the market.
Keywords: J23; J24; I23; 330; labor demand; skill demand; college major; educational investment